The Expected Impacts of Libya’s Accession to the World Trade Organization on Development and Reconstruction Efforts: Preliminary Conclusions (Journal of human and social sciences, 2023)
This study aims to highlight the nature and scope of the expected economic impacts of accelerating Libya’s accession to the World Trade Organization (WTO) on development and reconstruction efforts. To achieve this, the study reviewed the main features of the WTO, the membership-related steps Libya has previously taken or is expected to take, and provided an overview of the current state of the Libyan economy—its major characteristics and shortcomings that shaped its present condition. The research further examined the potential effects of full WTO membership and its implications for development and reconstruction, as well as the justifications for expediting the accession process. The findings indicate that full accession is no longer an optional choice but an urgent necessity driven by several factors in Libya’s favor. These include securing the benefits and rights of full membership granted to developing countries, improving revenues from hydrocarbons and petrochemical exports, reducing the rising costs of non-accession, creating a favorable environment for local and foreign investment, boosting foreign direct investment inflows, enhancing economic growth rates, reviving the stalled privatization program, and supporting reform, restructuring, and economic diversification to reduce structural dependence on the oil sector. Keywords: World Trade Organization – Development – Reconstruction – Libyan Economy.
Keywords: Libya's Accession to the WTO; Reconstruction; Economic Development; Economic Impacts; Trade Liberalization